2020
DOI: 10.7759/cureus.10859
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Hematological Risk Factors and Mortality Risk in Pediatric Arterial Ischemic Stroke: Analysis Report From Hospitals in the United States

Abstract: We aimed to analyze the differences in demographics, comorbidities, and the risk of in-hospital mortality in pediatric arterial ischemic stroke (PAIS) inpatient population by hematological (HEM) and cardiovascular (CV) risk factors. Methods A total of 4,036 inpatients (1-18 years of age) from the Nationwide Inpatient Sample (NIS) with a primary diagnosis of PAIS were included. Descriptive statistics, linear-by-linear association test, and logistic regression models were utilized to analyze differences in demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In-hospital mortality rate in childhood stroke has been reported with large variations, with a trend of the larger studies reporting lower mortality rates. Two relatively large cohorts present an in-hospital mortality of 3.1%-3.6% 75,77 whilst a 30-day mortality of almost 12% was seen in a single center Chilean study of 119 children. 76 The Canadian pediatric ischemic stroke register study showed a stroke specific mortality of 5% for pediatric ischemic stroke.…”
Section: Childhood Ischemic Strokementioning
confidence: 98%
See 1 more Smart Citation
“…In-hospital mortality rate in childhood stroke has been reported with large variations, with a trend of the larger studies reporting lower mortality rates. Two relatively large cohorts present an in-hospital mortality of 3.1%-3.6% 75,77 whilst a 30-day mortality of almost 12% was seen in a single center Chilean study of 119 children. 76 The Canadian pediatric ischemic stroke register study showed a stroke specific mortality of 5% for pediatric ischemic stroke.…”
Section: Childhood Ischemic Strokementioning
confidence: 98%
“…Mortality after pediatric ischemic stroke is assessed in a handful studies as the main research question. [72][73][74][75][76][77] Most studies evaluate hemorrhagic as well as ischemic stroke and include both perinatal and childhood cases. National register data from the United States used death certificates in children up to 20 years of age and showed a mortality rate of 0.09 per 100 000 person-years.…”
Section: Mortalitymentioning
confidence: 99%
“…8 Finally, we are unaware of any mortality studies in relatives of individuals with pediatric ischemic stroke despite that many risk factors for pediatric stroke and mortality thereafter have a hereditary component. 3,9 For these reasons, we performed a nationwide cohort study of >1600 children with stroke and their first-degree relatives to estimate overall and cause-specific mortality.…”
mentioning
confidence: 99%
“…Finally, we are unaware of any mortality studies in relatives of individuals with pediatric ischemic stroke despite that many risk factors for pediatric stroke and mortality thereafter have a hereditary component. 3,9…”
mentioning
confidence: 99%